Tracing awqaf mutawalli's accountability: some preliminary Malaysian evidence - Awaludin, Nur Suriana; Nahar, Hairul Suhaimi; Bakar, Nor Suhaily; Yaacob, Hisham (Institute for Strategic and Sustainable Accounting Development, Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia, 2016)
Mutawalli’s accountability is a pressing issue as it is inextricably linked to awqaf institution’s sustainability and survival. Being a manager to awqaf assets, mutawalli’s accountability is therefore expected to influence donators’ confidence and hence their continuous financial support. It is hence timely that mutawalli’s accountability from the acute dimensions of accounting and reporting are explored and examined. This effectively provides a basis for reality check for the necessary improvements. Consistent with the above, this study explores the current accounting and reporting practices of two distinct mutawallis operating on different operational platforms. Utilizing multiple research techniques comprising both, interviews and record reviews, the preliminary empirical results are arguably unique, systematically providing an appropriate basis for reality check on mutawalli’s accountability, thereby providing improvement framework on waqf management to other Malaysian mutawallis.